Markers of oxidative stress after three days of nanoTiO2 sunscreen use in humans: a pilot study - Pelclová, Daniela; Navrátil, Tomáš; Fenclová, Zdeňka; Vlčková, Štěpánka (Central European Journal of Public Health, 2020)
OBJECTIVE: Recent experimental studies point to a high reactivity of nanoparticles and the potential of sunscreens to penetrate the skin. We measured 20 markers of oxidative stress and inflammation to find out whether skin exposure to nanoTiO2 sunscreen may elevate the level of the markers in exhaled breath condensate (EBC) and urine of exposed subjects, as was suggested by our earlier study. METHODS: Six volunteers (3 males and 3 females), with a mean age of 48.0 ± 6.7 years, used commercial sunscreen for three days continuously. The first samples were collected before the test. The second samples were collected on day 4, before the sunscreen was washed off, and the third samples on day 11. The following biomarkers were measured: malondialdehyde, 4-hydroxy-trans-hexenal, 4-hydroxy-trans-nonenal, aldehydes C6-C12, 8-isoProstaglandin F2α, o-tyrosine, 3-chlorotyrosine, 3-nitrotyrosine, 8-hydroxy-2-deoxyguanosine, 8-hydroxyguanosine, 5-hydroxymethyl uracil, and leukotrienes B4, C4, D4, and E4, using liquid chromatography-electrospray ionisation-tandem mass spectrometry. RESULTS: In the urine, 4-hydroxy-trans-hexenal was significantly higher in post-exposure sample 2, and the same trend was seen in all urinary markers. In EBC, no difference was seen between the mean values of 20 post-test markers as compared with pre-test samples. CONCLUSION: This study suggests potential side effects of the sunscreen - borderline elevation of markers of oxidative stress/inflammation - which may relate to the absorption of the nanoTiO2, and the non-significant difference may be explained by the small number of subjects. The effect was not seen in EBC, where nanoTiO2 was not found. A larger study is needed, as according to our previous study, the beneficial effect of the sunscreen to suppress oxidative stress caused by UV radiation may be questioned.
Keywords: lidé středního věku; lidé; ženské pohlaví; Biomarkers; Female; mužské pohlaví; Adult; dechové testy; pilotní projekty; Middle Aged; Breath Tests; Pilot Projects; Humans; Sunscreening Agents; oxidační stres; biologické markery; dospělí; Male; Oxidative Stress; přípravky chránící proti slunci